Treatment Steps, Surgery, and Hospitalization Rates During the First Year of Follow-up in Patients with Inflammatory Bowel Diseases from the 2011 ECCO-Epicom Inception Cohort - Vegh, Z; Burisch, J; Pedersen, N; Kaimakliotis, I; Duricova, D; Bortlik, M; Vinding, K Kofod; Avnstrøm, S; Olsen, J; Nielsen, K R; Katsanos, K H; Tsianos, E V; et al. (Journal of Crohn's & colitis, 2015)
BACKGROUND AND AIMS: The ECCO-EpiCom study investigates the differences in the incidence and therapeutic management of inflammatory bowel diseases [IBD] between Eastern and Western Europe. The aim of this study was to analyse the differences in the disease phenotype, medical therapy, surgery, and hospitalization rates in the ECCO-EpiCom 2011 inception cohort during the first year after diagnosis. METHODS: Nine Western, five Eastern European centres and one Australian centre with 258 Crohn's disease [CD], 380 ulcerative colitis [UC] and 71 IBD unclassified [IBDU] patients [female/male: 326/383; mean age at diagnosis: 40.9 years, SD: 17.3 years] participated. Patients' data were registered and entered in the web-based ECCO-EpiCom database [www.epicom-ecco.eu]. RESULTS: In CD, 36 [19%] Western Europe/Australian and 6 [9%] Eastern European patients received biological therapy [p = 0.04], but the immunosuppressive [IS] use was equal and high in these regions [Eastern Europe vs Western Europe/Australia: 53% vs 45%; p = 0.27]. Surgery was performed in 17 [24%] CD patients in Eastern Europe and 13 [7%] in Western Europe/Australia [p < 0.001, pLogRank = 0.001]. Of CD patients from Eastern Europe, 24 [34%] were hospitalized, and 39 [21%] from Western Europe/Australia, [p = 0.02, pLogRank = 0.01]. In UC, exposure to biologicals and colectomy rates were low and hospitalization rates did not differ between these regions during the 1-year follow-up period [16% vs 16%; p = 0.93]. CONCLUSIONS: During the first year after diagnosis, surgery and hospitalization rates were significantly higher in CD patients in Eastern Europe compared with Western Europe/Australia, whereas significantly more CD patients were treated with biologicals in the Western Europe/Australian centres.
Keywords: dospělí; lékařská praxe - způsoby provádění; Europe; Female; Phenotype; kombinovaná terapie; surgery; Adult; ženské pohlaví; mladý dospělý; Colectomy; Australia; Inflammatory Bowel Diseases; lidé; Evropa; Immunosuppressive Agents; databáze faktografické; následné studie; kolektomie; hospitalizace; Austrálie; Middle Aged; Inflammatory bowel diseases; Incidence; prospektivní studie; Follow-Up Studies; Male; incidence; Aged; Combined Modality Therapy; Prospective Studies; Hospitalization; Young Adult; hospitalization; Databases, Factual; idiopatické střevní záněty; lidé středního věku; senioři; mužské pohlaví; fenotyp; imunosupresiva; Practice Patterns, Physicians'; Humans